2020
DOI: 10.1007/s11356-020-11335-5
|View full text |Cite
|
Sign up to set email alerts
|

Iterative classifier optimizer-based pace regression and random forest hybrid models for suspended sediment load prediction

Abstract: Suspended sediment load is a substantial portion of the total sediment load in rivers and plays a vital role in determination of the service life of the downstream dam. To this end, estimation models are needed to compute suspended sediment load in rivers. The application of artificial intelligence (AI) techniques has become popular in water resources engineering for solving complex problems such as sediment transport modeling. In this study, novel integrative intelligence models coupled with iterative classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 77 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Traditionally, the sediment rating curve (SRC), which is a fitted relationship between suspended sediment concentration and river water discharge, has been utilised to assess trends and obtain predictions of SSLs, albeit having long response times and requiring a lot of information. However, a branch of artificial intelligence known as machine learning (ML), has been shown to effectively address these issues 5 while producing more accurate SSL predictions compared to SRCs 1 3 , 9 11 . ML and deep learning, which is a more specialized version of ML typically consisting of neural networks, have also been used to solve important prediction problems within various fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the sediment rating curve (SRC), which is a fitted relationship between suspended sediment concentration and river water discharge, has been utilised to assess trends and obtain predictions of SSLs, albeit having long response times and requiring a lot of information. However, a branch of artificial intelligence known as machine learning (ML), has been shown to effectively address these issues 5 while producing more accurate SSL predictions compared to SRCs 1 3 , 9 11 . ML and deep learning, which is a more specialized version of ML typically consisting of neural networks, have also been used to solve important prediction problems within various fields.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the ANN and SVM, other algorithms have also been studied for the purpose of SSL prediction. Meshram et al 9 studied the iterative classifier optimizer-based pace regression (ICO-PR) and iterative classifier optimizer-based random forest (ICO-RF) for SSL prediction in the Seonath River basin, India. It was shown that the ICO-RF is more accurate than the ICO-PR, and stand-alone PR and RF models.…”
Section: Introductionmentioning
confidence: 99%
“…Linked to the hydrological and environmental evolutionary modeling, there exists a significant progress in suspended sediment transport modeling in recent years. Understanding the sediment transport process and modeling such a complex phenomenon are of importance in water resources management [29,30]. The suspended sediment concentration (SSC) in the river is a crucial problem in environmental, hydraulic, and water resources engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The major advantage of such SC techniques is that these models are fully nonparametric and do not require a priori concept of the relations between the input variables and the output data (Gocic ´et al 2015;Fahimi et al 2017). Various researchers have used ANNs for hydrologic studies including time series predictions of runoff or streamflow (Hsu et al 1995;Govindaraju 2000;Rajaee et al 2009Rajaee et al , 2010Melesse et al 2011;Lafdani et al 2013;Khan et al 2018;Meshram et al 2019aMeshram et al , 2019bMeshram et al , 2020Meshram et al , 2021aMeshram et al , 2021bMeshram et al , 2021cIraji et al 2020). Sudheer et al (2003) used radial-based neural networks for partial weather data; Trajkovic (2005) used radial-based neural networks using temperature-based models; Kisi (2007) applied a neural computing technique using climatic data; and Aytek (2008) applied a co-active neuro-fuzzy interpretation system.…”
Section: Introductionmentioning
confidence: 99%